Does green transition promote green innovation and technological acquisitions? - Udichibarna Bose; Wildmer Daniel Gregori; Maria Martinez Cillero (European Commission, 2023)
This analysis explores the implications of technological shifts towards greener and sustainable innovations on acquisition propensity between firms with different technological capacities. Using a dataset of completed control acquisition deals over the period of 2009-2020 from 23 OECD countries, we find that innovative firms are more likely to acquire innovative target companies. We also find that green acquirors (i.e., firms with green patents) are more inclined to enter into acquisition deals with green firms, possibly due to their technological proximity and informational advantages which further enhances their post-acquisition green innovation performances. Our results also show an increase in green acquisitions after the Paris Agreement by non-green acquiror firms, and these are more pronounced for acquirors in climate policy-relevant sectors and countries with low environmental standards than their counterparts. However, green acquisitions after the Paris Agreement do not show any significant impact on their post-acquisition innovation performances, raising concerns related to greenwashing behaviour by investing firms.
Keywords: G34; O30; Q54; Q55; 330; Acquisitions; Green patents; Firm Innovation; Paris Agreement; Green Transition